Optimal conditions of phospholipid produced from Bacillus subtilis (World Journal of Experimental Biosciences, 2014)
Phospholipid contains antimicrobial activity against different kinds of microorganisms. This article aimed to study the optimal conditions for the production and extraction of phospholipid produced from Bacillus subtilis. The result showed that the best production was obtained in NG medium containing 1% glucose, 50 μg/ ml tryptophan, pH 10, inoculated with 10% of bacterial culture and incubated at 30oC for 72 h in shaker incubator. The phospholipid was extracted with 50 % n-butanol three times, 10 % methanol, and then 10 % ethyl acetate. Fourier transform infrared spectroscopy (FTIR) analysis for B. subtilis Bf21 phospholipid showed peaks as 3460.06, 3359.77cm-1, 3228.62 cm-1, 2945.10 cm-1, 1728.68 cm-1, 1110.92 cm-1, and 1080,06 cm-1. These peaks indicate the presence of stretching (O-H, N-H, C-H, C=O, C-O, and P=O), which are functional groups present in phospholipid. Thin layer chromatography (TLC) analysis for B. subtilis Bf21 phospholipid was visualized after sprayed with spraying solution, as blue zone on a white background and Rf of phospholipid was 0.7.